The Ever-Evolving Landscape of Marketing Research for Air Transport and Tourism - Leonidou, Erasmia (My University, 2024)
Covid-19 pandemic affected the everyday life of the entire world and disrupted the global economy. Consequently, industries like air travel and tourism faced unprecedented upheavals and now all stakeholders need to navigate through these transformative changes. Based on this, marketing research becomes an essential tool for adapting and successfully navigating in this volatile environment. The chapter deals with this evolving landscape of marketing research and air transport within the tourism industry. In particular, the focus of this chapter is Marketing’s role in empowering airlines and tourism stakeholders to align to the changing needs of their customers in the evolving digital landscape, which is becoming fertile ground for environmentally conscious travel practices and innovative green strategies.
Marketing Solutions to the Challenges of a VUCA Environment
Keywords: Marketing research; Green Tourism; Digital transformation; Air transport